Importance of the water-sediment bed interactions in simulating microplastic particles in an estuarine system - Summers, Emily; Du, Jiabi; Park, Kyeong; Wharton, Marcus; Kaiser, Karl (Frontiers in Marine Science, 2024)
Retention of plastics in estuaries and storage in sediments likely contributes to the mass imbalance between the amount of ocean plastic debris and input from land. A sediment transport model, coupled with a hydrodynamic and wave model, was employed to analyze how microplastics of varying settling velocities behave under non-storm conditions and during extreme storm events in Galveston Bay, USA. The model was informed by measured concentrations of microplastics in a main tributary (Buffalo Bayou), which flows through the highly populated Houston-metro area. Under non-storm conditions, concentrations of neutrally buoyant particles are highest near the source location. In contrast, negatively buoyant particles are highest near the bay mouth where bed shear stress, and thus the potential for erosion/resuspension, is highest. Simulation of Hurricane Harvey, an unpreceded 1000-year flood event, shows a drastic increase of overall microplastic levels in Galveston Bay, approximately 5x that of non-storm conditions, and an increase in corresponding flux of microplastics to the Gulf of Mexico. The differences are attributed both to increases in microplastic loading and erosion of microplastics from bed sediments during Harvey. Differences in concentration between storm and non-storm conditions are most clear in the upper bay, where shear stress is low under normal conditions but shows a significant increase during storms due to wave-enhanced stress. Following Harvey, negatively buoyant particles levels return to normal in less than a week, but neutrally buoyant particle concentrations remain elevated over several months. Use of a sediment transport model that simulates erosion/resuspension to understand particle behavior lends further understanding of processes of microplastics not explored through previous use of particle tracking models that do not account for erosion/resuspension. This is of upmost importance for simulation of negatively buoyant particles, which have more potential to interact with the sediment bed layer. Variation of critical shear stress for erosion, erosion rate, and use of a wave model, all show significant impacts on particle behavior. Future parameterization of microplastic behavior in sediments will enhance our understanding of estuarine retention and export ability.